Additional file 2 of Intelligent identification of medical and veterinary intracellular protozoa by using self-supervised learning - Veerayuth Kittichai; Morakot Kaewthamasorn; Naruchit Soiphet; Teerawat Tongloy; Santhad Chuwongin; Siridech Boonsang (Figshare, 2026)
Supplementary Material 2.
Keywords: Machine Learning in Bioinformatics; AI in cancer detection; Digital Imaging for Blood Diseases